Comparative Study of Friction Models in High-Speed Machining of Titanium Alloys - Fan Yi; Ruoxi Zhong; Wenjie Zhu; Run Zhou; Li Guo; Ying Wang (Lubricants)
Friction has a significant impact on chip formation, so modeling it accurately is crucial in numerical cutting simulations. However, there is still controversy regarding the application scope and effectiveness of various friction models. A two-dimensional orthogonal cutting thermomechanical coupled finite element model is established. Critical strain values, recrystallization temperature, and recrystallization flow stress are introduced, and a power-law-modified softening coefficient is used to modify the standard Johnson–Cook constitutive model to simulate material mechanical properties. Zorev’s friction model, velocity-dependent friction model, and temperature-dependent friction model are separately employed to describe the friction behavior between the tool and workpiece. The contact and friction characteristics between the workpiece and tool, material damage, and temperature field are evaluated. Predicted cutting forces are compared and analyzed with experimental values. The friction coefficient can adjust the contact length between the tool and chip, the high-temperature range on the tool surface, and the fluctuation of temperature throughout the entire cutting process. The friction coefficient is more sensitive to sliding velocity, and the temperature distribution is more sensitive to the friction model than to different working conditions. Whether by modifying the friction coefficient or maximum friction shear stress, and regardless of whether adding parameters affected by velocity or temperature changes the fluctuation range, period, and local peaks of the cutting force prediction curve, improving the accuracy of predictions within certain working condition ranges to some extent. However, the overall trend of error fluctuations obtained from these friction models is similar, and the accuracy of predictions from these friction models tends to become more inaccurate with increasing cutting thickness.